Samuel Johnson : the arc of the pendulum - Johnston, Freya; Mugglestone, Lynda (Oxford : Oxford University Press, 2013)
This text offers wide-ranging coverage of Samuel Johnson's life work, and reception across 15 thematically cohesive chapters. Taking as its point of departure William Hazlitt's famous comparison between Johnson's prose style and a pendulum, this volume will contest and rebalance the metaphor of the pendulum.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Dec. 14, 2012).
Keywords: Johnson, Samuel, -- 1709-1784 -- Criticism and interpretation